2021
DOI: 10.1111/febs.15864
|View full text |Cite
|
Sign up to set email alerts
|

New roles for desmin in the maintenance of muscle homeostasis

Abstract: Desmin is the primary intermediate filament (IF) of cardiac, skeletal, and smooth muscle. By linking the contractile myofibrils to the sarcolemma and cellular organelles, desmin IF contributes to muscle structural and cellular integrity, force transmission, and mitochondrial homeostasis. Mutations in desmin cause myofibril misalignment, mitochondrial dysfunction, and impaired mechanical integrity leading to cardiac and skeletal myopathies in humans, often characterized by the accumulation of protein aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 111 publications
4
54
0
1
Order By: Relevance
“…The muscle-specific type III intermediate filament (IF) desmin is essential for a proper muscular structure and function. Because desmin IF connects adjacent myofibrils with each other as well as to the sarcolemma, nucleus and mitochondria, they are important for the mechanical and structural integrity of myofibrils [ 113 ]. Importantly, it has been shown that the loss of desmin IF during starvation- or denervation-induced atrophy precedes and promotes myofibril destruction [ 114 ].…”
Section: Protein Turnover In Muscle Is Regulated By a Precisely Acting Protein Degradation Pathwaymentioning
confidence: 99%
“…The muscle-specific type III intermediate filament (IF) desmin is essential for a proper muscular structure and function. Because desmin IF connects adjacent myofibrils with each other as well as to the sarcolemma, nucleus and mitochondria, they are important for the mechanical and structural integrity of myofibrils [ 113 ]. Importantly, it has been shown that the loss of desmin IF during starvation- or denervation-induced atrophy precedes and promotes myofibril destruction [ 114 ].…”
Section: Protein Turnover In Muscle Is Regulated By a Precisely Acting Protein Degradation Pathwaymentioning
confidence: 99%
“…Intermediate filaments. Desmin is one of the major cytoplasmic intermediate filaments in the skeletal muscle and maintains mechanical integrity during contraction [ 181 ]. Mutations in desmin cause desmin-related myopathy (OMIM#601419) and cardiomyopathy (OMIM#604765).…”
Section: Common Pathomechanisms Of Cnmsmentioning
confidence: 99%
“…Mutations in desmin cause desmin-related myopathy (OMIM#601419) and cardiomyopathy (OMIM#604765). Desmin localizes to Z-disk, where it plays a key role in the integration and maintenance of the structure and function of striated muscle [ 181 ]. Specifically, desmin anchors several structures (mitochondria, nucleus, and Z-disk) to the sarcolemma cytoskeleton at the costamere and regulates peripheral nuclei positioning in myofibers [ 182 ].…”
Section: Common Pathomechanisms Of Cnmsmentioning
confidence: 99%
“…Compromising effects of Dsg2 mutation on cell mechanics are most likely mediated through altered desmosomal cell-cell adhesion at the intercalated disc and changes in the three-dimensional organization of the desmosome-anchored desmin intermediate filament network. The latter forms a complex scaffold for organelles and myofibrils [ 73 , 74 , 75 ]. The recently observed considerably altered desmin organization in Dsg2 mutants during embryonic cardiogenesis with detrimental consequences on cardiac differentiation and function underscores the importance of an intact desmin network for cellular integrity [ 76 ].…”
Section: Discussionmentioning
confidence: 99%